Audit exposes grade fraud. (Times Higher Education Supplement, 2007)
The article focuses on the charges filed against Elvin Escano, a computer laboratory technician at a New York community college, for taking alcohol and cash from students in exchange for using the college's computer to change their grades. The defendant was charged with 137 counts of grand larceny, falsifying business records, computer tampering and forgery.